Depression, Anxiety, Coping Skills and Quality of Life Among Pre-University Students in Kuantan Pahang - Siti Roshaidai Mohd Arifin; Aisyah Wahidah Yuhasri’Azan; Amalia Kamaruddin; Hazwani Mohd Mohadis; Karimah Hanim Abd Aziz; Ramli Musa; Noor Azimah Muhammad; Khadijah Hasanah Abang Abdullah; Fathima Begum Syed Mohideen; Mohd Fadzli Marhusin; Khairi Che Mat; Hanisah Mohd Noor; et al. (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2025)
Index (Tier 2)